EFFECTS OF INTERNAL CONTROL SYSTEM ON THE ORGANIZATOINAL PERFORMANCE OF REMITTANCE COMPANIES IN MODADISHU-SOMALIA - MIRE, HASSAN ADAM; Mukhongo, aaron (IJRDO - Journal of Business Management, 2016)
The purpose of this research would be to examine the effect of internal control system practice on the performance of remittance companies in Mogadishu-Somalia. The study would adopt a quantitative research with the specific research design being a descriptive design. The population of the study is the classified remittance companies locate in Bakara market, and they were 15 remittance companies in Bakara market, the employees worked that 15 remittance companies are 402 employees.The sampling technique use would be purposive sampling. Primary data would collect by use of questionnaires which are administered through drop and pick method. Data screening would be done to identify any missing data and it would be further test for reliability and normality. Data would be analyzing using SPSS version.The study recommended that there is need for the remittance companies in Mogadishu to increase their control environment; risk assessment and control activity as it was founded that these variables positively affects the organizational performance of remittance companies in Mogadishu.